Analisis Hukum terhadap Dampak Pengenaan Tarif 32% oleh Amerika Serikat terhadap Perdagangan Indonesia : Tinjauan Perjanjian Perdagangan Internasional dan Kebijakan Ekonomi - Muhammad Sultan Mandalika; Vanessa Debora Muaja (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the impact of the 32% tariff imposed by the United States on Indonesian goods, as well as its legal implications within the context of international trade agreements signed by Indonesia. The two main research questions addressed are: first, how does the imposition of this 32% tariff affect Indonesia's trade balance; and second, what are the legal implications of this tariff policy in the context of international trade agreements, and how can it influence Indonesia's position in global trade negotiations. The analysis reveals that the tariff is likely to reduce Indonesia's export volume to the U.S. market, potentially leading to a significant decline in trade surplus. From a legal perspective, such action may violate provisions of the Trade and Investment Framework Agreement (TIFA) and fundamental principles established under the General Agreement on Tariffs and Trade (GATT). This protectionist policy could undermine the competitiveness of Indonesian products in international markets and create uncertainty for business actors. The study recommends strategic measures for the Indonesian government, including renegotiating with the U.S., diversifying export markets, and enhancing domestic product competitiveness to address challenges posed by this tariff policy. Thus, it is hoped that Indonesia can strengthen its position in global trade negotiations despite facing unilateral policies that are detrimental to its economic interests.